Dc motor speed control by using pulse width modulation / Muhammad Zul Affendy Abu Bakar - Abu Bakar, Muhammad Zul Affendy (2001)
Today, there are many types of dc motor controller that had been designed. Engineers had designed new methods of speed control which improve the performance of the motor. Motor controllers are very important especially to dc motors where they are used currently in many industries. Dc motors have several variable characteristics and are used extensively in variable speed drives. They also can provide a high starting torque and also possible to obtain speed control over wide range. The methods of speed control are normally simpler and less expensive than those of ac drives. In this project, speed control using Pulse Width Modulation (PWM) is designed using a power electronic circuit. The development of advanced power electronics switching devices [1] enable high frequency switching operations and has improved the performance of PWM inverter for driving a dc motor. This method is more effective and efficient compared to the traditional method controller where the speed of dc motor is controlled by varying the amplitude of voltage. The design of the circuit is simulated by Orcad Release 9 Software before fabricating into hardware.